SIMPLIFIED WAYANG PERFORMANCE AS A MEDIUM OF TEACHING OF INDONESIAN LESSON FOR FOREIGN SPEAKER (BIPA) IN ISLAMIC UNIVERSITY (PTKI) IN FACING INDUSTRY 4.0 REVOLUTION ERA - Isnaniah, Siti (Al Qalam, 2019)
This paper is aimed to analyze how wayang can be used as a medium of teaching BIPA in PTKI in facing industry 4.0 revolution era. Wayang (shadow puppet) as learning media of BIPA can be applied in industry 4.0 revolution era in advanced level by using a simplified performance of wayang as a learning media. The method in this research was descriptive analytic method. The techniques of collecting the data included documentary techniques and content analysis. The data were analysed, described,  and concluded. The techniques of analysis data used Literature Based Thematic (LBT) and interactive model. LBT, a model of literature appreciation, is applied in learning the simplified wayang performance. This model will lead students to learn literature as a way of life. Students watch wayang performance in a film together in Indonesian language, then students discuss the good things or character education that need to be implemented or not in life, students are also asked to compare the characters each other, after that the students write the results of the discussion in Indonesian language and they will have a peer-review activity to evaluate their work.